2015
DOI: 10.1158/2326-6066.cir-14-0138
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Restrains Radiotherapy-Induced Abscopal Effect

Abstract: We investigated the influence of PD-1 expression on the systemic antitumor response (abscopal effect) induced by stereotactic ablative radiotherapy (SABR) in preclinical melanoma and renal cell carcinoma models. We compared the SABRinduced antitumor response in PD-1-expressing wild-type (WT) and PD-1-deficient knockout (KO) mice and found that PD-1 expression compromises the survival of tumor-bearing mice treated with SABR. None of the PD-1 WT mice survived beyond 25 days, whereas 20% of the PD-1 KO mice survi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
268
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(275 citation statements)
references
References 30 publications
4
268
1
2
Order By: Relevance
“…Immune checkpoint inhibitors can strengthen the antitumor immune function caused by radiotherapy, especially as the latter increases the expression of PD-L1 on tumor cells [19]. In fact, combined blockade of PD-1 and CTLA-4 during radiotherapy demonstrated a significant therapeutic effect in both irradiated and non-irradiated large-burden tumors in vivo [20]. However, the possibility that ipilimumab alone might have been responsible for the aforementioned patient's response cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Immune checkpoint inhibitors can strengthen the antitumor immune function caused by radiotherapy, especially as the latter increases the expression of PD-L1 on tumor cells [19]. In fact, combined blockade of PD-1 and CTLA-4 during radiotherapy demonstrated a significant therapeutic effect in both irradiated and non-irradiated large-burden tumors in vivo [20]. However, the possibility that ipilimumab alone might have been responsible for the aforementioned patient's response cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…94 However, the abscopal effect is rare to occur in patients with metastatic cancer, possibly because of inappropriate fractionation dose or blockade of antitumor response that is supposed to be triggered by radiotherapy. 95 Thus, an optimal combination to maximize the abscopal effect is urgently needed. In terms of NSCLC, combining PD-1/PD-L1 antibodies rather than CTLA-4 antagonists with radiotherapy are more feasible to induce the abscopal effect.…”
Section: Combined With Radiotherapymentioning
confidence: 99%
“…Preclinical studies confirmed that upregulation of PD-1 limited the radiotherapy-induced abscopal effect and PD-1 blockade effectively potentiated the immune response. 95 Recently, a phase II study was ongoing to evaluate the combination of nivolumab and radiosurgery in cancer patients, including renal cell carcinoma and NSCLC, with brain metastases. The patients involved in the trial are planned to receive nivolumab 240 mg (q2w) intravenously and radiosurgery with customized dose from 15 to 20 Gy will be delivered after the first dose of nivolumab (NCT02978404).…”
Section: Combined With Radiotherapymentioning
confidence: 99%
“…The combination of local radiotherapy and immunemodulation can augment local tumor control and cause distant antitumor effects (abscopal), increasing tumor-antigen release and antigen-presenting cell (APC) cross-presentation, improving dendritic cell (DC) function, and enhancing T cell priming (110)(111)(112)(113) (Figure 2). On the other hand, ionizing radiation can also generate chemotactic signals that recruit several myeloid-cell types with distinct roles in T cell suppression (114)(115)(116).…”
Section: Multimodality Treatments and Future Directionsmentioning
confidence: 99%